Against Medical Advice Discharges in Injection and Non-injection Drug Use-associated Infective Endocarditis: A Nationwide Cohort Study. (5th August 2020) - Kimmel, Simeon D; Kim, June-Ho; Kalesan, Bindu; Samet, Jeffrey H; Walley, Alexander Y; Larochelle, Marc R
Abstract: Background: Among those with injection drug use-associated infective endocarditis (IDU-IE), against medical advice (AMA) discharge is common and linked to adverse outcomes. Understanding trends, risk factors, and timing is needed to reduce IDU-IE AMA discharges. Methods: We identified individuals ages 18–64 with International Classification of Diseases, 9 th Revision, diagnosis codes for infective endocarditis (IE) in the National Inpatient Sample, a representative sample of United States hospitalizations from January 2010 to September 2015. We plotted unadjusted quarter-year trends for AMA discharges and used multivariable logistic regression to identify factors associated with AMA discharge among IE hospitalizations, comparing IDU-IE with non-IDU-IE. Results: We identified 7259 IDU-IE and 23 633 non-IDU-IE hospitalizations. Of these hospitalizations, 14.2% of IDU-IE and 1.9% of non-IDU-IE resulted in AMA discharges. More than 30% of AMA discharges for both groups occurred before hospital day 3. In adjusted models, IDU status (adjusted odds ratio [AOR], 3.92; 95% confidence interval [CI], 3.43–4.48)] was associated with increased odds of AMA discharge. Among IDU-IE, women (AOR, 1.21; 95% CI, 1.04–1.41) and Hispanics (AOR, 1.32; 95% CI, 1.03–1.69) had increased odds of AMA discharge, which differed from non-IDU-IE. Over nearly 6 years, odds of AMA discharge increased 12% per year for IDU-IE (AOR, 1.12; 95% CI, 1.07–1.18) and 6% per year for non-IDU-IE (AOR, 1.06; 95% CI. 1.00–1.13). Conclusions: AMA discharges have risen among individuals with IDU-IE and non-IDE-IE. Among those who inject drugs, AMA discharges were more common and increases sharper. Efforts that address the rising fraction, disparities, and timing of IDU-IE AMA discharges are needed. Abstract : In this national cohort, against medical advice (AMA) discharges grew, affecting one-fifth of injection drug use-associated infective endocarditis (IDU-IE) hospitalizations. Odds of AMA discharge were 4 times higher for IDU-IE versus non-IDU-IE; one-third occurred before hospital day 3.